Registration of Establishments (Laying Hens) Regulations (Northern Ireland) 2003 : Notification of changes to details held on the Register.: Notification of changes to details held on the Register. ([2017]) - Northern Ireland., Department of Agriculture, Environment; Rural Affairs
No abstract available